Engaging Colonial Knowledge
XI, 306 p.
Keywords: Presenting a set of rich case-studies which demonstrate novel and productive approaches to the study of colonial knowledge, this volume covers British, Danish, Dutch, French, German, Portuguese, and Spanish colonial encounters in Africa, Asia, America and the Pacific, from the sixteenth to the twentieth century.